Olfactory function and neurocognitive outcomes in old age: The Atherosclerosis Risk in Communities Neurocognitive Study - Palta, Priya; Chen, Honglei; Deal, Jennifer A; Sharrett, A Richey; Gross, Alden; Knopman, David; Griswold, Michael; Heiss, Gerardo; Mosley, Thomas H (Alzheimer's & dementia, 2018)
We tested the hypothesis that poor sense of smell is associated with lower cognitive function and higher mild cognitive impairment (MCI) prevalence. Olfaction, measured by the Sniffin' Sticks test, was categorized as olfactory impairment (OI) (score ≤6) or no OI (score >6). MCI was adjudicated based on review of a neuropsychological examination. Linear regression estimated the mean difference in cognitive factor scores, and log-binomial regression quantified MCI prevalence among participants with versus without OI. Participants with OI had lower mean factor scores (memory: -0.27 standard deviation [SD], 95% confidence interval [CI]: -0.35 to -0.19; language: -0.24 SD, 95% CI: -0.30 to -0.17; executive function/processing speed: -0.09 SD, 95% CI: -0.12 to -0.06; and general cognitive performance: -0.25 SD, 95% CI: -0.30 to -0.20). OI was also associated with MCI (n = 204; prevalence ratio = 1.56, 95% CI: 1.37, 1.78). An impaired sense of smell may serve as a readily accessible early marker of neurodegeneration and improve upon the prevailing delayed diagnoses and underascertainment of MCI/dementia.